DEVELOPMENT OF TOURISM IN KARAKALPAKSTAN ON THE BASIS OF DIGITAL TECHNOLOGIES (Web of Technology: Multidimensional Research Journal, 2025)
This article analyzes the current state of the tourism sector in the Republic of Karakalpakstan and considers the possibilities of developing tourism services using digital technologies. The article pays special attention to the types of digitization, advanced foreign experiments and the possibilities of their application to the conditions of Karakalpakstan.